Comparative Secretome Analysis of Mesenchymal Stem Cells From Dental Apical Papilla and Bone Marrow During Early Odonto/Osteogenic Differentiation: Potential Role of Transforming Growth Factor-β2 - Yu, Shi; Li, Jingzhi; Zhao, Yuming; Li, Xiaoxia; Ge, Lihong (Frontiers in Physiology, 2020)
To understand the functions of secretory proteins in odontogenesis and to further the understanding of the different molecular events during odontogenesis and osteogenesis, we induced the odonto/osteogenic differentiation of stem cells from dental apical papilla (SCAPs) and bone marrow-derived stem cells (BMSCs) in vitro, and compared the expression of secretory proteins during early odonto/osteogenic differentiation using high-performance liquid chromatography with tandem mass spectrometry. The results revealed significant changes by at least 50% in 139 SCAPs proteins and 203 BMSC proteins during differentiation. Of these, 92 were significantly upregulated and 47 were significantly downregulated during the differentiation of SCAPs. Most of these proteins showed the same trend during the differentiation of BMSCs. Among the proteins that showed significantly changes during the differentiation of SCAPs and BMSCs, we found that transforming growth factor-β2 (TGFβ2) is a key protein in the network with powerful mediation ability. TGFβ2 was secreted more by SCAPs than BMSCs, was significantly up-regulated during the differentiation of SCAPs and was significantly down-regulated during the differentiation of BMSCs. Furthermore, the effects of recombinant human TGFβ2 and TGFβ1 on the odonto/osteogenic differentiation of SCAPs and BMSCs were investigated. Real-time RT-PCR and western blot analyses demonstrated that TGFβ2 enhanced the odontogenic-related markers (DSPP, DMP1) and inhibited the osteogenic-related markers BSP in SCAPs, whereas TGFβ1 enhanced the BSP expression and inhibited the DSPP and DMP1 expression at early odonto/osteogenic differentiation of SCAPs. However, in BMSCs, TGFβ2 enhanced the expression of ALP, RUNX2, DSPP and DMP-1, whereas TGFβ1 enhanced the expression of ALP and RUNX2, with no significant intergroup difference of DSPP at the early odonto/osteogenic differentiation of BMSCs. TGFβ2 is a potentially important molecule with a distinct function in the regulation of odontogenesis and osteogenesis.